2015
DOI: 10.3389/fmicb.2015.00821
|View full text |Cite
|
Sign up to set email alerts
|

Paracoccidioides spp. ferrous and ferric iron assimilation pathways

Abstract: Iron is an essential micronutrient for almost all organisms, including fungi. Usually, fungi can uptake iron through receptor-mediated internalization of a siderophore or heme, and/or reductive iron assimilation (RIA). Traditionally, the RIA pathway consists of ferric reductases (Fres), ferroxidase (Fet3) and a high-affinity iron permease (Ftr1). Paracoccidioides spp. genomes do not present an Ftr1 homolog. However, this fungus expresses zinc regulated transporter homologs (Zrts), members of the ZIP family of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Finally, recent investigations have provided additional perspectives for RIA. In Paracoccidioides species, whose genome does not encode an FTR1 iron permease, the authors suggested that the fungus utilizes a nonclassical FTR1-independent RIA system that requires Fe/Zn permeases, known as Zrts, that may account for iron uptake (68), adding an additional layer of complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent investigations have provided additional perspectives for RIA. In Paracoccidioides species, whose genome does not encode an FTR1 iron permease, the authors suggested that the fungus utilizes a nonclassical FTR1-independent RIA system that requires Fe/Zn permeases, known as Zrts, that may account for iron uptake (68), adding an additional layer of complexity.…”
Section: Discussionmentioning
confidence: 99%
“…1a, b) described more in detail in our previous publication [35]. Microorganisms can assimilate iron through receptormediated internalization of a water soluble siderophore (low molecular weight ferric ion-specific chelator) or heme and/or reductive iron assimilation [38,39]. To the best of our knowledge, the mechanism of iron uptake by Metschnikowia yeasts is not elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the presence of iron for the human pathogenic Paracoccidioides species also influences virulence, although no detailed study is available about the MCOs of this particular fungus. Only in silico analyses suggest that PAAG_06004 and PADG_05994 could encode functional ferroxidases [90]. Laccases also play an important role in fungal pathogens by generating mainly melanin.…”
Section: Discussionmentioning
confidence: 99%